VORTEX CONVERTER OF CONTINUOUS MEDIUM FLOW - Serebryakov, R. (Енергетика і автоматика, 2016)
The problems of conversion of solar and wind energy, as well as the use of hydro energy laminated swirling flows can play an important role in connection with the thermal-hydraulic feature of these trends, concentrating in the swirl jet flows kinetic energy scattered in the surrounding area. This allows the use of low-potential thermal ascending flow induced by solar heating, weak wind and kinetic energy flows in rivers and water channels.